Software quality : concepts and practice - Galin, Daniel (John Wiley & Sons, IEEE Press, 2017)
The book presents a comprehensive discussion on software quality issues and software quality assurance (SQA) principles and practices, with special emphasis on implementing and managing SQA. Primarily designed to serve three audiences: universities and college students, vocational training participants, and software engineers and development managers, the book may be applicable to all personnel engaged in software projects. Features: . A broad view of SQA- The book delves into SQA issues, going beyond the classic boundaries of custom-made software development to also cover in-house software development, subcontractors, and ready made software.. An up-to-date wide-range coverage of SQA and SQA related topics- Provides comprehensive coverage on multifarious SQA subjects, including topics hardly explored until SQA texts. . A systematic presentation of the SQA function and its tasks- Establishes the SQA processes, planning, coordinating, follow-up, review, and evaluation of SQA processes.. Focus on SQA implementation issues- Includes specialized chapter sections, examples, implementation tips, and topics for discussion. . Pedagogical support- Each chapter includes a real-life mini case study, examples, a summary, selected bibliography, review questions, and topics for discussion.